Primitiveness in Paul Klee’s printmaking’s art works (Damascus University Journal for engineering sciences, 2023)
Primitiveness is considered one of the most important aesthetic concepts in the modern art in the twentieth century. With it began the shift towards the fundamental vision in art which is stemmed from instinct and primitive sense, when simplicity and serenity express the artist's creativity and essence, Paul Klee accomplished unique works characterized by the ability to express and renewable creativity, this led to show the importance of primitiveness in a contemporary style. Klee’s experiences were an example of uniqueness which based on the primitive art, which characterized by simplified line, color, and movement .So Paul Klee was considered a genius in the modern art and an important representative for modern controversial currents because of his adventurous spirit, Paul Klee presented his works in a new visual way which combined the simplicity of primitive art and the modern artistic methods, especially in the field of graphics, starting from the first beginning until the reach of the completed work.
Keywords: Primitiveness; Primitive art; printmaking; Paul Klee Childish art